Flexing, Mukbang dan Paylater dalam Sorotan Hadis: Membaca Ulang Konsep Isrāf - Najah, Muftihun (Journal of Hadith Studies, 2024)
This research is motivated by the fact that consumptive behavior (excessive consumption) has become a significant issue in the modern era. In the Prophetic traditions, this behavior is referred to as isrāf, which encompasses not only primary but also basic human needs. Several hadiths of the Prophet Muhammad (peace be upon him) explicitly prohibit isrāf, including those narrated by al-Nasā’ī (No. 2512), Ibn Mājah (No. 3595), and Aḥmad (No. 6408). Accordingly, this study aims to examine these prohibitive hadiths by employing a combination of Yusuf al-Qaradawi’s maʿānī al-ḥadīth framework and Jean Baudrillard’s theory of consumerism, to assess the relevance of the prohibition of isrāf within the context of contemporary consumption patterns. This study addresses three main research questions: (1) What is the concept of isrāf in the hadiths? (2) How are these hadiths understood in the present context? (3) What is the relevance of the concept of isrāf to modern consumer behavior? The findings of this study are threefold. First, in the Prophetic traditions, isrāf refers to behavior that exceeds actual necessity, whether in terms of wealth expenditure or other aspects of life. According to scholars, isrāf applies not only to monetary spending but also to any action that exceeds reasonable limits. Second, the hadiths prohibiting isrāf emphasize the importance of maintaining balance and avoiding extravagance—be it in eating, dressing, or spending—especially in a modern context where media and technology encourage consumptive behavior. Third, isrāf has evolved in form in contemporary society. For instance, isrāf in food consumption is manifested through the mukbang trend on social media, isrāf in clothing is reflected in the phenomenon of flexing, and isrāf in financial expenditure is influenced by the PayLater payment method. These phenomena illustrate how the concept of isrāf remains relevant and identifiable in various dimensions of modern consumer behavior.